Éponges hypercalcifées ('Pharétronides', 'Sclérosponges') des cavités des récifs coralliens de Nouvelle-Calédonie. - Vacelet, J. (Bulletin du Muséum national d’Histoire naturelle (4, A), 1981)
Nineteen species of sponges with reinforced skeletons, belonging to the polyphyletic groups of « Pharetronids )) and « Sclerosponges )), were found in small, dark cavities of the coral reefs of Noumea (New Caledonia). Five of them are described as new species in the family Minchinellidae (Calcarea). A key to the species of the recent Minchinellidae is given and a new classification of the hypercalcified sponges is pl'oposed. These sponges are relict species of diverse sponge groups which were reef-builders up to the Cretaceous